Challenges and choices for crime-fighting technology : federal support of state and local law enforcement - Schwabe, William, 1942- (Rand, 2001)
This report provides findings of a study of technology in use or needed by law enforcement agencies at the state and local level, for the purpose of informing federal policymakers as they consider technology-related support for these agencies.
"Supported by the office of Science and Technology Policy and the National Institute of Justice."
"MR-1349-OSTP/NIJ"--Page 4 of cover
Keywords: Law enforcement -- Technological innovations -- United States.; Law enforcement -- United States -- Administration.; Federal aid to law enforcement agencies -- United States.; Forensic sciences -- United States.; Lois -- Application -- Innovations -- États-Unis.; Lois -- Application -- États-Unis -- Administration.; Criminalistique -- États-Unis.; POLITICAL SCIENCE -- Political Freedom & Security -- Law Enforcement.; TECHNOLOGY & ENGINEERING -- General.; Federal aid to law enforcement agencies; Forensic sciences; Law enforcement -- Administration; Law enforcement -- Technological innovations; United States